PENGARUH KESESUAIAN KOMPENSASI, PENGENDALIAN INTERNAL DAN GOOD CORPORATE GOVERNANCE TERHADAP PENCEGAHAN FRAUD - Hadi Samanto; Yuwita Ariessa Pravasanti; Sinta Agus Saputra (Jurnal Akuntansi dan Pajak, 2022)
This research aims to find out the effect of Compensation Suitability, Internal Control and Good Corporate Governance on Fraud Prevention in Syariah Solo Hotels. The type of data used in this study is primary data in the form of compensation conformity questionnaires, internal control and Good Corporate Governance affecting fraud prevention. The population used in this study is all employees consisting of each Department in Hotel Syariah Solo as many as 88 Karywan. Sampling using the formula Slovin and obtained a sample of 47 respondents. The data anlaisis technique uses multiple linear regression analysis with the help of the SPSS program version 18.00. Results of analysis of research data: 1) Conformity of compensation, internal control and Good Coroporate Government simultaneously had an effect of 52.7% on fraud prevention in Hotel Syariah Solo; 2) The suitability of compensation has no significant effect on fraud prevention in Hotel Syariah Solo; 3) Internal control has no significant effect on the variables of fraud prevention in Hotel Syariah Solo; and 4) There is a significant influence on Good Corporate Government on fraud prevention variables.